Reassessment of Species Diversity of the Subfamily Denticollinae (Coleoptera: Elateridae) through DNA Barcoding - Han, Taeman; Lee, Wonhoon; Lee, Seunghwan; Park, In Gyun; Park, Haechul (PLOS ONE, 2016)
The subfamily Denticollinae is a taxonomically diverse group in the family Elateridae. Denticollinae includes many morphologically similar species and crop pests, as well as many undescribed species at each local fauna. To construct a rapid and reliable identification system for this subfamily, the effectiveness of molecular species identification was assessed based on 421 cytochrome c oxidase subunit I (COI) sequences of 84 morphologically identified species. Among the 84 morphospecies, molecular species identification of 60 species (71.4%) was consistent with their morphological identifications. Six cryptic and/or pseudocryptic species with large genetic divergence (>5%) were confirmed by their sympatric or allopatric distributions. However, 18 species, including a subspecies, had ambiguous genetic distances and shared overlapping intra- and interspecific genetic distances (range: 2.12%–3.67%) suggesting incomplete lineage sorting, introgression of mitochondrial genome, or affection by endosymbionts, such as Wolbachia infection, between species and simple genetic variation within species. In this study, we propose a conservative threshold of 3.6% for convenient molecular operational taxonomic unit (MOTU) identification in the subfamily Denticollinae based on the results of pairwise genetic distances analyses using neighbor-joining, mothur, Automatic Barcode Gap Discovery analysis, and tree-based species delimitation by Poisson Tree Processes analysis. Using the 3.6% threshold, we identified 87 MOTUs and found 8 MOTUs in the interval between 2.5% to 3.5%. Evaluation of MOTUs identified in this range requires integrative species delimitation, including review of morphological and ecological differences as well as sensitive genetic markers. From this study, we confirmed that COI sequence is useful for reassessing species diversity for polymorphic and polytypic species occurring in sympatric and allopatric distributions, and for a single species having an extensively large habitat.